Impact of disinfection processes on bacterial community in urban wastewater: Should we rethink microbial assessment methods? - Cesare, Andrea Di (2021)
The development of new methods and technologies for microbial characterization as well as their increasing availability at more affordable costs, has made evident the limitations of the conventional and routinely applied (typically cultivation based) methods to exhaustively and fully characterize the actual effect of disinfection process in urban wastewater treatment plants (UWWTPs). Such problem is even more relevant and of concern if microbial challenges, such as the occurrence of pathogens as well as the spread of antibiotic resistance, are taken into account. Such threats move scientists to investigate new and more effective disinfection processes from one side and new methods, techniques and approaches to characterize disinfection process efficiency from the other side. In this opinion paper, the limitations of routine detection methods are discussed according to the relevant and updated scientific literature to explain how research oriented methods and technologies (namely, quantitative real-time PCR, flow cytometry, metagenetics and metagenomics) can allow a better evaluation of disinfection processes. After a short introduction to the main disinfection processes, the application of different microbial characterization methods is discussed according to distinct challenges, such as pathogens inactivation or antibiotic resistance dissemination, when wastewater safety is of concern (for example in reuse scenarios). The routine and research oriented techniques can be successfully used in complementary way to evaluate disinfection process efficiency. Recommendations for UWWTPs managers for internal control of disinfection process are proposed.